Efektivitas Model Pembelajaran RME (Realistic Mathematic Education) Terhadap Hasil Belajar pada Materi Operasi Hitung Perkalian Siswa Kelas III SD Muhammadiyah Ambarketawang 1 - Tias Lesinia Yusita; Saputro, Hengkang Bara (Mandalika Mathematics and Educations Journal, 2023)
Mathematics learning on multiplication calculation operations material that fully involves students optimally. Students are expected to be able to instill the concept of multiplication and relate it to everyday life. This activity has an impact on student learning outcomes in multiplication calculation operations material so this research aims to determine the influence of the learning model Realistic Mathematic Education (RME) Regarding Learning Results in Multiplication Calculation Operations Material for Class III Students at SD Muhammadiyah Ambarketawang 1. This research method uses a quantitative approach, the type of research used ispre-experiment with research designone group pretest-posttest design. The sample in this study was class IIIA, totaling 21 students consisting of 12 female students and 9 male students. Data collection techniques using observation, tests and documentation. Data analysis techniques use normality, homogeneity and hypothesis testing. The results of the data analysis test showed that there were changes in student learning outcomes before the learning model was implementedRME (Realistic Mathematic Education) after carrying out the learning modelRME (Realistic Mathematic Education). Based on these results, the effectiveness of the learning modelRME (Realistic Mathematic Education) on Mathematics learning outcomes in multiplication arithmetic operation material for class III students at SD Muhammadiyah Ambarketawang 1.